Respon Pertumbuhan Bayam ( Amaranthus sp ) Terhadap Pemberian Trichoderma sp Di Desa Babul Makmur - Nonita Sari; Amda Resdiar; Irvan Subandar; Jasmi Jasmi (Jurnal Agrotek Lestari, 2023)
This study aims to determine the Growth Response of Spinach (Amaranthus sp) to Trichoderma sp administration in Babul Makmur Village by applying Trichoderma sp fertilizer with Dakota and Sumatra 901 varieties and to determine the interaction of Spinach Plant Growth Response (Amaranthus sp) with Trichoderma sp fertilizer application. This research is a field trial carried out in Babul Makmur Village, Simeulue Barat District, Simeulue Regency. The study was conducted from November to December 2022, using the factorial pattern RAK (Randomized Block Design). The first factor is the dose of Trichoderma sp which consists of 3 levels, namely T1 = 30gr/plot, T2 = 40gr/plot, and T3 = 50gr/plot. The second factor of spinach plant varieties consisted of 2 types, namely V1 = Dakota variety and V2 = Sumatra 901 variety. The parameters observed were Plant Height (cm), Number of Leaves (strands), Root Length (cm), Wet Fallow (gr), Weight Dry (gr). From the results of the parameters observed, it can be concluded that the best results from applying Trichoderma sp. and types of varieties on plant height parameters were found in the T2V2 treatment, in the number of leaves parameter T2V1, in the root length parameter T3V1, in the wet weight parameter T3V1 and in the dry weight parameter T1V1 had better growth than other treatments.